2021
DOI: 10.1016/j.jlr.2021.100082
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 deletion of ORMDLs reveals complexity in sphingolipid metabolism

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Immunoblotting with a pan ORMDL antibody that detects all isoforms (22) showed that the interaction with ORMDLs was completely abolished by the ex2del variant which lacks the whole TMD (Figure 2A). The other variants affecting the SPTLC1-TMD, L39del and F40S41del, showed a diminished interaction with ORMDLs, while Y23F retained interaction with ORMDLs (Figure 2A).…”
Section: Ormdls Fail To Interact With Sptlc1 Variantsmentioning
confidence: 99%
“…Immunoblotting with a pan ORMDL antibody that detects all isoforms (22) showed that the interaction with ORMDLs was completely abolished by the ex2del variant which lacks the whole TMD (Figure 2A). The other variants affecting the SPTLC1-TMD, L39del and F40S41del, showed a diminished interaction with ORMDLs, while Y23F retained interaction with ORMDLs (Figure 2A).…”
Section: Ormdls Fail To Interact With Sptlc1 Variantsmentioning
confidence: 99%
“…For quantification, total sphingolipids were extracted and quantified by high-resolution mass spectrometry. The interaction of ORMDLs with SPT inhibits SPT activity, as knockdown (Fig 2D), (22) or knockout (23) of all three ORMDLs leads to increased SL synthesis. In contrast, while the expression of SPTLC1 variants L39del and ex2del in SPTLC1-KO cells led to an overall increase in SL synthesis compared to WT-SPTLC1 expressing cells, silencing ORMDLs had little or no effect on the activity of the L39del and ex2del variant (Fig 2E), suggesting that increased SL synthesis by the variants is primarily caused by dysfunctional feedback inhibition rather than by an increased activity of the holoenzyme.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the SPTLC2 N terminus determines the localization of the protein, as it alone can target both ER and mitochondria ( Fig 1F ). Regulatory subunits ORMDL1-3 and ssSPTa-b control SPT activity and acyl-chain specificity ( Han et al, 2009 ; Breslow et al, 2010 ; Harmon et al, 2013 ; Green et al, 2021 ). Structural studies reveal details of the interaction of the regulatory subunits with the SPT-complex, and these protein interactions may also play a role in determining SPT localization and activity.…”
Section: Resultsmentioning
confidence: 99%